Modelo de los cinco factores de personalidad: análisis personológico comparativo de adolescentes - Torres Ullauri, Cinthia Carolina (My University, 2019)
In the eagerness of granting a broad vision to Psychology, Gordon Allport establishes the Theory of Traits; focused on individual differences and the development of instruments to measure personality dimensions. Following this current, Costa Jr. and McCrae propose the Model of the Five Personality Factors, to organize in five dimensions: neuroticism, extraversion, openness to experience, kindness and responsibility; the attitudinal and behavioral tendencies that characterize individuals. It has been shown that this taxonomic model allows to describe and identify the personal characteristics of the adolescent population, in order to strengthen the functional features and prevent risk behaviors. Therefore, the objective of this essay was to make a comparative-personological analysis of the protagonists of the film "The Breakfast Club", through the use of a bibliographical descriptive research methodology. The observation of audiovisual material together with the literature review of the Model of the Five Personality Factors of Costa Jr. and McCrae, detailed in the Neo Revised Personality Inventory NEO PI-R, and the Baumrind and Maccoby’s classification of parenting styles, allowed to establish an approach to the personality trends of protagonists. In the film it was evident that the characters, particularly through a fragile period in their lives to be immersed in an unfavorable family and institutional context, characteristics that influence the personality and behaviors developed throughout the plot.
En el afán de otorgar una visión amplia a la Psicología, Gordon Allport instaura la Teoría de los Rasgos; enfoque centrado en las diferencias individuales y en la elaboración de instrumentos para medir las dimensiones de personalidad. Siguiendo esta corriente, Costa Jr. y McCrae proponen el Modelo de los Cinco Factores de Personalidad, para organizar en cinco dimensiones: neuroticismo, extraversión, apertura a la experiencia, amabilidad y responsabilidad; las tendencias actitudinales y comportamentales que caracterizan a los individuos. Se ha demostrado que este modelo taxonómico posibilita describir e identificar las características personológicas de la población adolescente, para así fortalecer los rasgos funcionales y prevenir conductas de riesgo. Por tal razón, el presente ensayo tuvo como objetivo realizar el análisis personológico comparativo de los protagonistas de la película “El club de los cinco”, a través de la utilización de la metodología de investigación bibliográfica descriptiva. La observación de material audiovisual junto con la revisión del Modelo de los Cinco Factores de Personalidad de Costa Jr. y McCrae, detallado en el Inventario de Personalidad Neo Revisado NEO PI-R, y la clasificación de los estilos de crianza de Baumrind y Maccoby, permitieron establecer una aproximación a las tendencias de personalidad de los protagonistas. En el film se pudo evidenciar que los personajes, particularmente atraviesan por un periodo frágil en su vida al estar inmersos en un contexto familiar e institucional desfavorable, características que influyen en la personalidad y comportamientos desarrollados a lo largo de la trama.
Keywords: TEORIA; PERSONALIDAD; RASGO; ADOLESCENCIA